Solution and surface-confined chloride anion templated redox-active ferrocene catenanes - Evans, N; Rahman, H; Leontiev, A; Greenham, N; Orlowski, G; Zeng, Q; Jacobs, R; Serpell, C; Kilah, N; Davis, J; Beer, P (2012)
The first examples of ferrocene containing catenanes, in solution and assembled on a surface are described. Chloride anion templation is exploited to synthesize redox-active [2]- and [3]-catenanes via Grubbs' ring closing metathesis, utilizing a novel ferrocene-appended isophthalamide macrocycle. X-ray crystal structures of both catenanes were determined. The ability of the [2]catenane to selectively bind and characteristically sense its chloride anion template is demonstrated by use of 1H NMR and electrochemical voltammetric techniques. Self-assembled monolayers of analogous surface-confined catenanes have been prepared on gold. In addition to being characterized by cyclic voltammetry and ellipsometry, detailed information regarding the structure of the catenane monolayers has been provided by use of angle integrated high resolution X-ray photoelectron spectroscopy. This journal is © 2012 The Royal Society of Chemistry.